Isobavachalcone exhibits antifungal and antibiofilm effects against C. albicans by disrupting cell wall/membrane integrity and inducing apoptosis and autophagy - Qian, Weidong; Lu, Jiaxing; Gao, Chang; Liu, Qiming; Yao, Wendi; Wang, Ting; Wang, Xiaobin; Wang, Zhifeng (Frontiers in Cellular and Infection Microbiology, 2024)
Isobavachalcone (IBC) is a natural flavonoid with multiple pharmacological properties. This study aimed to evaluate the efficacy of IBC against planktonic growth and biofilms of Candida albicans (C. albicans) and the mechanisms underlying its antifungal action. The cell membrane integrity, cell metabolic viability, and cell morphology of C. albicans treated with IBC were evaluated using CLSM and FESEM analyses. Crystal violet staining, CLSM, and FESEM were used to assess the inhibition of biofilm formation, as well as dispersal and killing effects of IBC on mature biofilms. RNA-seq combined with apoptosis and autophagy assays was used to examine the mechanisms underlying the antifungal action of IBC. IBC exhibited excellent antifungal activity with 8 μg/mL of MIC for C. albicans. IBC disrupted the cell membrane integrity, and inhibited biofilm formation. IBC dispersed mature biofilms and damaged biofilm cells of C. albicans at 32 μg/mL. Moreover, IBC induced apoptosis and autophagy-associated cell death of C. albicans. The RNA-seq analysis revealed upregulation or downregulation of key genes involved in cell wall synthesis (Wsc1 and Fks1), ergosterol biosynthesis (Erg3, and Erg11), apoptisis (Hsp90 and Aif1), as well as autophagy pathways (Atg8, Atg13, and Atg17), and so forth, in response to IBC, as evidenced by the experiment-based phenotypic analysis.These results suggest that IBC inhibits C. albicans growth by disrupting the cell wall/membrane, caused by the altered expression of genes associated with β-1,3-glucan and ergosterol biosynthesis. IBC induces apoptosis and autophagy-associated cell death by upregulating the expression of Hsp90, and altering autophagy-related genes involved in the formation of the Atg1 complex and the pre-autophagosomal structure. Together, our findings provide important insights into the potential multifunctional mechanism of action of IBC.